Assessment risk of work-related musculoskeletal disorders according to the RULA method in Nurses - Santos, Paula Clara (2018)
In what concerns Occupational Health, the most recurrent injuries are musculoskeletal disorders, which are frequently associated with risk factors, such as, repetition of the task and handling of loads. Among health professionals, nurses are the most affected.